The Literacy Habituation to Grow Early Childhood Language Skills Through Picture Story Books in Early Childhood Education - Hidayat, Linda Fasha; Nandiyanto, Asep Bayu Dani; Kurniawan, Tedi; Bilad, Muhammad Roil (LPPM Universitas Jenderal Achmad Yani, 2021)
Literacy is a language skill possessed by someone in communicating. Literacy habituation needs to be done from an early age because it will make children accustomed to literacy which will also be able to cultivate their imagination. At this time, many parties apply literacy to early childhood with an inappropriate process, some children are required to be able to read and write in a method that requires children to think hard. By using picture storybook media, it will foster children's literacy skills. In this quantitative method, the authors take samples from several children with observational data collection techniques, namely interviews and questionnaires. The results of data collection stated that eight out of ten children succeeded in following the literacy habits that the authors applied. Therefore, literacy is very important to be applied to early childhood so that children can have the ability to communicate effectively that can develop their potential and participate in community life in the future.